Azimuthal anisotropy of heavy-flavor decay electrons in p-Pb collisions at √sNN=5.02 TeV - Acharya, Shreyasi; Angelov, Venelin; Arslandok, Mesut; Danisch, Meike; Deisting, Alexander; Feuillard, Victor; Glässel, Peter; Kim, Jiyoung; Kim, Minjung; Klewin, Sebastian; Köhler, Markus Konrad; Leardini, Lucia; et al. (Physical review letters, 2019)
Angular correlations between heavy-flavor decay electrons and charged particles at midrapidity (|η|<0.8) are measured in p-Pb collisions at √sNN=5.02 TeV. The analysis is carried out for the 0%-20% (high) and 60%-100% (low) multiplicity ranges. The jet contribution in the correlation distribution from high-multiplicity events is removed by subtracting the distribution from low-multiplicity events. An azimuthal modulation remains after removing the jet contribution, similar to previous observations in two-particle angular correlation measurements for light-flavor hadrons. A Fourier decomposition of the modulation results in a positive second-order coefficient (v2) for heavy-flavor decay electrons in the transverse momentum interval 1.5<pT<4 GeV/c in high-multiplicity events, with a significance larger than 5σ. The results are compared with those of charged particles at midrapidity and those of inclusive muons at forward rapidity. The v2 measurement of open heavy-flavor particles at midrapidity in small collision systems could provide crucial information to help interpret the anisotropies observed in such systems.
ALICE Collaboration: S. Acharya, V. Anguelov, M. Arslandok, H. Beck, M.C. Danisch, A. Deisting, V.J.G. Feuillard, P. Glässel, J. Kim, M. Kim, S. Klewin, M.K. Köhler, L. Leardini, J. Mercado Perez, A. Ohlson, Y. Pachmayer, K. Reygers, R. Schicker, M.O. Schmidt, J. Stachel, D.F. Weiser, B. Windelband [und weitere]
Im Titel steht der Ausdruck "sNN" unter dem Wurzelsymbol, "NN" ist dabei tiefgestellt
Gesehen am 10.04.2019